Whole rock basalt alteration from CO2-rich brine during flow-through experiments at 150 °C and 150 bar - Luhmann, A; Tutolo, B; Tan, C; Moskowitz, B; Saar, M; Seyfried, W (Elsevier, 2017)
Four flow-through experiments at 150 °C were conducted on intact cores of basalt to assess alteration and mass transfer during reaction with CO2-rich fluid. Two experiments used a flow rate of 0.1 ml/min, and two used a flow rate of 0.01 ml/min. Permeability increased for both experiments at the higher flow rate, but decreased for the lower flow rate experiments. The experimental fluid (initial pH of 3.3) became enriched in Si, Mg, and Fe upon passing through the cores, primarily from olivine and titanomagnetite dissolution and possibly pyroxene dissolution. Secondary minerals enriched in Al and Si were present on post-experimental cores, and an Fe2O3-rich phase was identified on the downstream ends of the cores from the experiments at the lower flow rate. While we could not specifically identify if siderite (FeCO3) was present in the post-experimental basalt cores, siderite was generally saturated or supersaturated in outlet fluid samples, suggesting a thermodynamic drive for Fe carbonation from basalt-H2O-CO2 reaction. Reaction path models that employ dissolution kinetics of olivine, labradorite, and enstatite also suggest siderite formation at low pH. Furthermore, fluid-rock interaction caused a relatively high mobility of the alkali metals; up to 27% and 100% of the K and Cs present in the core, respectively, were preferentially dissolved from the cores, likely due to fractional crystallization effects that made alkali metals highly accessible. Together, these datasets illustrate changes in chemical parameters that arise due to fluid-basalt interaction in relatively low pH environments with elevated CO .